2007
DOI: 10.2320/matertrans.n-mra2007862
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Reactivity Index to Propose Intra and Intermolecular Reactivity in Metal Cluster Interaction over Oxide Surface

Abstract: The hard soft acid-base (HSAB) principles classify the interaction between acids and bases in terms of global softness. In last few years the reactivity index methodology is well established and had found its application in a wide variety of systems. This study aims to propose the viability of the reactivity index to monitor metal cluster interaction with oxide surface with a description of the theory developed. We have chosen pure gold cluster from a size between 2 to 12 to be interacted with clean alumina (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In particular, one problem of drug design is that one has to synthesize and screen thousands, sometimes millions, of candidate chemicals in developing one successful drug. There was a very successful study with reactivity index long back on human immunodeficiency virus (HIV) [88]. The The comparison between the biological activity and global softness shows a better correlation, suggesting that polarization effects dominate over the CT contribution in the interaction between the so-called hinge region and the ligand.…”
Section: Study On Cdk2 Inhibitors Using Global Softnessmentioning
confidence: 99%
“…In particular, one problem of drug design is that one has to synthesize and screen thousands, sometimes millions, of candidate chemicals in developing one successful drug. There was a very successful study with reactivity index long back on human immunodeficiency virus (HIV) [88]. The The comparison between the biological activity and global softness shows a better correlation, suggesting that polarization effects dominate over the CT contribution in the interaction between the so-called hinge region and the ligand.…”
Section: Study On Cdk2 Inhibitors Using Global Softnessmentioning
confidence: 99%
“…Pure gold cluster of a size between 2 and 12 was chosen to interact with clean alumina (100) surface. A scale was derived in terms of intra-and intermolecular interactions of gold cluster with alumina surface to rationalize the role of reactivity index in material designing [94]. We have calculated the relative nucleophilicity and electrophilicity for the clusters in the middle of the table, left hand side is for pure clusters and right hand side is for the clusters adsorbed over alumina surface.…”
Section: Prediction Of Interaction Between Metal Clusters With Oxide mentioning
confidence: 99%
“…It is found that the relative strength of donors depends on the nature of acceptor and vice versa, but many other factors may be involved. Hard Soft Acid Base (HSAB) classification is often used to rationalize some of strength difference [6] . Hard acid prefer hard base and soft acid prefer soft base.…”
Section: Introductionmentioning
confidence: 99%